Hydraulic redistribution: limitations for plants in saline soils. (7th August 2017) - Bazihizina, Nadia; Veneklaas, Erik J.; Barrett‐Lennard, Edward G.; Colmer, Timothy D.
Abstract: Hydraulic redistribution (HR), the movement of water from wet to dry patches in the soil via roots, occurs in different ecosystems and plant species. By extension of the principle that HR is driven by gradients in soil water potential, HR has been proposed to occur for plants in saline soils. Despite the inherent spatial patchiness and salinity gradients in these soils, the lack of direct evidence of HR in response to osmotic gradients prompted us to ask the question: are there physical or physiological constraints to HR for plants in saline environments? We propose that build‐up of ions in the root xylem sap and in the leaf apoplast, with the latter resulting in a large predawn disequilibrium of water potential in shoots compared with roots and soil, would both impede HR. We present a conceptual model that illustrates how processes in root systems in heterogeneous salinity with water potential gradients, even if equal to those in non‐saline soils, will experience a dampened magnitude of water potential gradients in the soil–plant continuum, minimizing or preventing HR. Finally, we provide an outlook for understanding the relevance of HR for plants in saline environments by addressing key research questions on plant salinity tolerance. Abstract : Despite significant water potential gradients in saline soils owing to large differences in soil water osmotic potentials within the root‐zone of individual plants, no conclusive evidence exists for hydraulic redistribution (HR) in such conditions. This paper advances the hypothesis that build‐up of ions in root xylem sap and in the leaf apoplast acts to diminish HR‐driving water potential gradients. As a result, plants in spatially heterogeneous saline soils with osmotic‐dominated gradients in water potential appear to have little HR.